SIMPLE-G: A multiscale framework for integration of economic and biophysical determinants of sustainability. (November 2020) - Baldos, U.L.C.; Haqiqi, I.; Hertel, T.W.; Horridge, M.; Liu, J.
Abstract: We introduce SIMPLE-G, a Simplified International Model of agricultural Prices, Land use, and the Environment- Gridded version, which is a novel tool for evaluating sustainability policies in a global context while factoring in local heterogeneity in land and water resources and natural ecosystem services. This multi-scale model can provide boundary conditions for local decision makers, as well as capturing feedback from local policies to national and global scales. To illustrate its value in environmental analysis, we provide two applications of the model. First, we quantify the local stresses on land and water resources due to global changes in population, income, and productivity. Second, we quantify the global impacts of local policy responses and adaptations to water scarcity. Graphical abstract: Image 1 Highlights: Novel global-to-local-to-global modelling framework introduced. Model condensation permits rapid solution with millions of grid cells. GeoHub implementation allows users to run the model and explore results via the web. Subtotals allow for attribution of local stresses to individual global change drivers .